Analisis Kinerja Keuangan Pada Lembaga Persekutuan Pelayanan Kristen Untuk Kesehatan Di Indonesia - Grace Gloria; Ahmad Tomu (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2023)
This study aims to determine the financial performance of Christian service associations for health in Indonesia/PELKESI from the aspects of revenue management efficiency, program activity management efficiency, non-program activity financing efficiency. This research is a descriptive research with data collection techniques through observation and documentation. Data analysis instruments use income efficiency ratios or fiscal performance, program activity ratios, non-program activity ratios. The results of the analysis show that PELKESI's financial performance from the aspect of income management results of the analysis is classified as poor, the lowest ratio analysis results occurred in 2017, namely 90%, from the aspect of program activity management efficiency it is classified as efficient, the highest ratio analysis results occurred in 2018 of 63% , and from the aspect of non-program financing it is classified as very efficient, the highest ratio analysis result was in 2017 of 79%.